Deniz İş Kanunu Kapsamında Çalışan İşçilerin Yıllık Ücretli İzin Hakkı - (:unkn) unknown (My University, 2018)
Türk İş Hukuku’nda, gemiadamlarının çalışmailişkileri 854 s. Deniz İş Kanunu’nda düzenlenmiş-tir. Söz konusu Kanun, diğer birçok konuda ol-duğu gibi bu konuda da, 4857 s İş Kanunundanfarklı olarak, ayrıntılı düzenlemeler içermemek-tedir. Bu nedenle, yıllık ücretli izne hak kazanma,yıllık iznin fiilen kullanılması, yıllık izin ücreti, bir-den fazla iş sözleşmesine dayalı olarak çalışmaveya işyerinin devrinin yıllık izin hakkına etkisi, işsözleşmesinin sona ermesinin kullandırılmayanyıllık ücretli izin haklarına etkisi ve zamanaşımıgibi konuların Deniz İş Kanunu yönünden ayrıcadeğerlendirilmesi gerekmektedir. Aşağıda, buçerçevede konu incelenmiştir.

In Turkish Labour Law, seamen’s employ- ment relations are regulated by Maritime Labour Code, No. 854. The Code, as in many other subjects, in contrast to Labour Code, No. 4857, does not include detailed provi- sions in this subject. Therefore, annual leave rights, exercice of annual leave rights, annual paid leave working on more than one em- ployment contract or the effect of the busi- ness transfers to the annual leave rights, the effect of employment contract’s termination on remaining annual leave with pay rights and statute of limitations need to be evalu- ated in respect of Maritime Labour Code. The subject is addressed within this framework below.
Annual Paid Leave Rights of the Employees Who Work in the Scope of Maritime Labour Code
Keywords: Hukuk